Comparative evaluation of cephalometric measurements of monitor-displayed images by Nemoceph software and its hard copy by manual tracing - Tripti Tikku; Rohit Khanna; R.P. Maurya; Kamna Srivastava; Rastra Bhushan (Journal of Oral Biology and Craniofacial Research)
Objective: The aim of this study was to evaluate and compare the cephalometric measurements obtained from computerized tracing of direct digital radiographs and hand tracing of their digital radiographic printouts. Material and methods: The soft- and hard-copies of pre-treatment lateral cephalograms of 40 subjects (both males and females) within the age group of 10–30 years, irrespective of the type of malocclusion were taken. Total 26 measurements (13 linear and 13 angular) were obtained using both the manual and the digital technique. Results: Amongst the linear measurements, Anterior facial height (AFH), Posterior facial height (PFH), Upper lip length (ULL), Lower lip length (LLL), Anterior cranial base length (ACBL), Posterior cranial base length (PCBL), Maxillary length (MxL), Mandibular length (MdL), Lower incisor to NB line (L1 to NB) and Lower lip protrusion (LLP) showed statistically significant difference between the two techniques but were clinically acceptable (difference between the digital and manual technique were less than 2 units (1 unit = 1 mm for linear measurements and 1° for angular measurements). While amongst the angular measurements, only occlusal plane angle showed statistically significant difference between the two techniques that was not clinically acceptable. Conclusion: Digital measurements obtained from monitor-displayed images (soft copy) were found to be reproducible and comparable to the manual method done on its hard copy, for all the measurements except occlusal plane angle (SN-occlusal plane).